Orbital evolution of meteorite-producing groups and their sources - Горбанев, Ю.М.; Коновалова, Н.А.; Давруков, Н.Х. (Radiotekhnika, 2020)
This paper presents and discusses findings from the study of orbital evolution of six meteorite-producing groups, which include meteorites known from instrumental observations. The existence of four meteorite-producing groups was studied earlier by Halliday et al. using data from the Meteorite Observation and Recovery Project (MORP) network in Canada and the Prairie Network (PN) in USA. We have inferred the asteroidal origin of some fireball streams. Shestaka investigated a swarm of meteorite-forming bodies containing the Innisfree and Ridgedale fireballs. The study yielded that the examined swarm contained nine small meteoric swarms, several asteroids and 12 fireballs photographed by the cameras of the Prairie Network and Canadian Meteorite Observation and Recovery Project. The investigation of the annual activity profile of bright sporadic fireballs from the International Astronomical Union Meteor Data Centre (IAU MDC) database and small meteors (from -2.5 to -5.0 mag) from the SonataCo database resulted in the identification of several peaks in the fireball activity which were not related to any recognised cometary meteor showers. Such results gave an impetus to further study the issue of the existence of groups of sporadic meteoroids and L3.5-H5 ordinary chondrites in Jupiter-family comet-like orbits in the near-Earth space and their relationship with their plausible parents, i.e. near-Earth objects (NEOs). The relationship between meteorite-producing groups and their plausible parents was verified by the backwards analysis of the evolution of the mean orbit of each meteorite-producing group, a known meteorite and their plausible parent NEOs over a time span of several millennia. The analysis was carried out using the Halley software whereby the equations of motion were numerically integrated using the 11th-order Everhart method.